Institutional capabilities for scientific-technological linkage at a state management university - Di Meglio, Fernanda (2017)
From a theoretical perspective from political science, this article identifies and analyzes the various institutional capacities involved in the development of policy linkage in a state-run university Argentina. The empirical data on which this study is based were generated through documentary analysis from the university under study and supplemented with semi-structured interviews applied to various officials in the subject. The results show that the university developed institutional capacities linked to the creation of a structure of ad hoc interaction that serves as the link between the territory and the university, and the implementation of a policy of incentives to promote community participation academic in these activities as well as the involvement of the university in public and private spaces and the active leadership of the university managers responsible for this function.